Fabrication of polypyrrole/β-MnO2 modified graphite felt anode for enhancing recalcitrant phenol degradation in a bioelectrochemical system. (1st August 2017) - Chen, Dan; Shen, Jinyou; Jiang, Xinbai; Mu, Yang; Ma, Dehua; Han, Weiqing; Sun, Xiuyun; Li, Jiansheng; Wang, Lianjun
Graphical abstract: Highlights: One-step electrodeposition of PPy/β-MnO2 onto GF electrode was first investigated. Recalcitrant phenol degradation was enhanced in BES using PPy/β-MnO2 /GF anode. Higher current and higher CE was achieved in BES using PPy/β-MnO2 /GF anode. The key role of β-MnO2 in phenol degradation and power generation was explored. Abstract: In order to develop a highly efficient anode material for recalcitrant phenol degradation in bioelectrochemical system (BES), fabrication of polypyrrole (PPy)/β-MnO2 composite onto graphite felt (GF) electrode through facile one-step electrodeposition was investigated in this study. The successful coating of PPy/β-MnO2 onto GF surface was verified by scanning electron microscopy, Raman spectrum and XPS. The improved electrochemical property of the GF electrode modified by PPy/β-MnO2 was confirmed by cyclic voltammetry analysis, chronoamperometric and electrochemical impedance spectra. The application of PPy/β-MnO2 modified GF electrodes in BES notarized the superior degradation performance towards phenol. Shorter startup time, higher mineralization efficiency and improved bacteria adhesion was achieved in BES using PPy/β-MnO2 modified GF as anode. Coulombic efficiencies of 17.3 ± 0.5% in BES using PPy/β-MnO2 modified GF as anode was much higher than those in BES using PPy modified GF and blank GF as anode, which were as low as 12.1 ± 2.4% and 6.6 ± 1.3%, respectively. The key role of MnO2 and possible degradation pathway involved in phenol degradation was further proposed. The milder fabrication condition, improved electrochemical activity and increased phenol degradation efficiency suggest that PPy/β-MnO2 /GF has a promising future in BES application for recalcitrant phenol catalytic degradation.